Seasonal occurrence of chilli (Capsicum annuum L.) diseases in Kerala, India - DEVI, SALLY K MATHEW, M ABDUL WAHAB, S NIRMALA (Journal of Spices and Aromatic Crops, 1995)
Observations on the seasonal occurrence of chilli (Capsicum annuum L.) diseases in Vellanikkara, Trichur, India during 1989 to 1991 showed that Alternaria leaf blight, die back and fruit rot diseases were serious problems during rainy season. Incidence of leaf blight (Phytophthora capsici) and bacterialleafspot (Xanthomonas campestris pv. vesicatoria) were also observed in this area.